2002
DOI: 10.1046/j.1475-1313.2002.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

The multifocal electroretinogram in central serous chorioretinopathy

Abstract: The multifocal ERG can be used to evaluate retinal dysfunction in CSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 6 publications
0
32
1
Order By: Relevance
“…35,48,111,149,151,172,187,229,232,292--294,305,329 During acute CSC, retinal dysfunction is reflected by reduction in mfERG response amplitudes and delay in implicit times. 35,111,187,305 Marmor and Tan demonstrated that mfERG response amplitudes were not only depressed in areas of serous retinal detachment but also extended beyond the area of detachment. 187 This suggests a more widespread area of retinal dysfunction occurs as compared with the localized subretinal fluid seen clinically.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%
“…35,48,111,149,151,172,187,229,232,292--294,305,329 During acute CSC, retinal dysfunction is reflected by reduction in mfERG response amplitudes and delay in implicit times. 35,111,187,305 Marmor and Tan demonstrated that mfERG response amplitudes were not only depressed in areas of serous retinal detachment but also extended beyond the area of detachment. 187 This suggests a more widespread area of retinal dysfunction occurs as compared with the localized subretinal fluid seen clinically.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%
“…[13][14][15][16][17] Most previous studies have been performed under photopic conditions, which are thought to reflect mainly conemediated photoreceptor and bipolar function. 18,19 Although reduced amplitudes and delayed latency of the cone mfERG have been demonstrated with age [20][21][22] and in different stages of ARM [23][24][25][26] mainly with concentric ring averaging methods, there have been no studies identifying the functional impairment of rods. Recently Hood et al 27 developed a mfERG protocol for isolating rod responses in humans and Holopigian et al 28,29 demonstrated the clinical use of this protocol in retinitis pigmentosa and progressive cone dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in patients with unsteady fixation, implicit times are the most suitable parameters for diagnosis [17,22]. In addition, during the interpretation of the results, attention should be paid to those cases with unsteady fixation which would mask the real result [11].…”
Section: Discussionmentioning
confidence: 99%